Chest radiography in adult critical care unit: A pictorial review - Jain, Sanjay N (Indian J Radiol Imaging, 2019)
Patients in the intensive care units suffer from a myriad of cardiopulmonary processes for which portable chest radiography is the most utilized imaging modality. A pragmatic approach toward evaluating the nearly similar radiographic findings seen in most of the pathologies with comparative review and strong clinical acumen can help the radiologists and clinicians achieve a rapid and precise diagnosis.